Costing improved water supply systems for low-income communities : a practical manual - Carlevaro, Fabrizio; Gonzalez, Cristian (IWA Publishing, 2015)
This manual and the free downloadable costing tool is the outcome of a project identified by the Water, Sanitation and Health Programme (WSH) of the World Health Organization (WHO) faced with the challenge of costing options for improved access, both to safe drinking water and to adequate sanitation.